KEKUATAN MAKNA UNGKAPAN BIJAK DALAM NOVEL-NOVEL TERE LIYE: KAJIAN SEMANTIK - H, Rahmawati; Said, Ikhwan M.; Abbas, Asriani (Universitas Hasanuddin, 2018)
The research aimed at elaborating: (1) the wise expression forms in wise the novels of Tere Liye’s “Rindu” and “Pukat”, (2) the implicit meaning in the wise expression, and (3) the meaning strength of the wise expression in the conversations, so that the meaning contents could be found out. This was the qualitative descriptive research with the semantic analysis. Data resources were Tere Liye’s novels. The research data were in the forms of the wise expressions found in the conversations. The data were collected thought the scrutinized method with the note-taking technique. The data were analysed descriptively through the concepts of Leech and Djajasudarma. The research result indicates that Tere Liye are forty two wise expression used in both novels. The wise expression forms are the advice, ethic/moral, educational, and religious wise expression. The wise expression which are frequently used in the novel “Rindu” are the advice and religious wise expression, similarly the wise expressions which are frequently used in the novel “Pukat” are the ethic/moral expression. The wise expression meanings in the novel “Rindu” include the narrowed, widened, connotative, emotive, lexical, propositional, pictorial, idiomatic meaning, whereas the wise expression meanings in the novel “Pukat” include the widened, connotative, lexical, propositional, pictorial, and idiomatic meanings. The wise expression meaning strength in the novel “Rindu” usedthe conversations include the conceptual, connotative, stylistic, affective, and thematic, meanings. Similarly the meaning strength found in the novel “Pukat” include the conceptual, connotative, affective,reflective, and thematic.